PENGARUH PEMBERITAAN SURAT KABAR TERHADAP PERSEPSI MASYARAKAT PENGGUNA JASA TRANSPORTASI UDARA DI SURABAYA (Kasus Studi Kecelakaan Pesawat Adam Air) - Elton, Lydia (Institute of Research and Community Outreach - Petra Christian University, 2007)
Cases of aircraft accidents that have been frequently exposed in mass media both print-and-electronic media have led its news to spread expansively among societies.